INSTITUTIONAL INTEGRATED TELETANDEM: STUDENTS' PERCEPTIONS ABOUT COLLABORATIVE WRITING - Spatti Cavalari, Suzi Marques [UNESP] (Unesp-faculdade Ciencias & Letras, 2016)
Institutional integrated teletandem (iiTTD) is characterized as a series of teletandem sessions that are embedded in regular FL lessons (thus mandatory) so that such lessons both feed and are fed by teletandem practice (CAVALARI; ARANHA, [2016]). Collaborative writing is conceived as an activity in which learners work together throughout the process of planning, generating ideas, structuring, editing and revising a text in the foreign language (STORCH, 2013). This paper aims at (i) describing a collaborative writing task that was implemented within iiTTD at UNESP - Sao Jose do Rio Preto, and (ii) discussing Brazilian learners' perceptions as they carried out such task in 2015. Data were collected by means of learning diaries written by thirteen students of English as a foreign language who were taking a Translation Studies major.
Keywords: Collaborative writing; Institutional integrated teletandem; Learner's perceptions